Optasia: A Relational Platform for Efficient Large-Scale Video Analytics - Lu, Yao; Chowdhery, Aakanksha; Kandula, Srikanth (SoCC '16, Santa Clara, CA, USA, 2016)
Camera deployments are ubiquitous, but existing methods to analyze video feeds do not scale and are error-prone. We describe Optasia, a dataflow system that employs relational query optimization to efficiently process queries on video feeds from many cameras. Key gains of Optasia result from modularizing vision pipelines in such a manner that relational query optimization can be applied. Specifically, Optasia can (i) de-duplicate the work of common modules, (ii) auto-parallelize the query plans based on the video input size, number of cameras and operation complexity, (iii) offers chunk-level parallelism that allows multiple tasks to process the feed of a single camera. Evaluation on traffic videos from a large city on complex vision queries shows high accuracy with many fold improvements in query completion time and resource usage relative to existing systems. Click here for some detailed examples and a demo.